Knowledge, Attitude, and Practice Regarding 3R (Reduce, Reuse and Recycle) and its Associated Factors among School Students in Bangladesh: A Cross-Sectional Study - Hasan, Rakin; Ghapor, Adilah Abdul; Moniruzzaman, Md.; Mamun, Abu Sayed Md. Al (Journal of Sustainability and Environmental Management, 2024)
Efficient waste management is crucial for maintaining a healthy environment, and young generations play a vital role in this process by practicing the 3R principle. Therefore, this study aimed to investigate the knowledge, attitudes, and practices (KAP) and its associated factors among secondary school students regarding the 3R. The two-stage random sampling method collected information from 400 students to investigate their KAP concerning 3R awareness. Statistical analyses such as descriptive statistics, Chi-square, and logistic regression were applied in this study. This study discovered that among students, 54.50% knew 3R, 58.50% showed a positive attitude towards it, and 51.12% practiced 3R principles. Urban students demonstrated higher knowledge, positive attitude, and better practice of 3R compared to rural students. Belonging to a joint family increased the likelihood of possessing 3R knowledge compared to nuclear families, but individuals from joint families were less likely to have a positive attitude towards 3R. Additionally, male students and those aged 13 years and above were more likely to have 3R knowledge than their counterparts. This study revealed different levels of understanding, positive attitudes, and actual implementation of 3R principles among the participants, with various factors influencing their KAP. It emphasizes raising awareness among young students or similar groups to promote sustainable waste management and environmental conservation efforts.